(untitled) (Research, Society and Development, 2021)
The present study aims to evaluate the presence of strains of coagulase-positive Staphylococcus (SCP) in the service environment of the Dental School Clinic of the Federal University of Campina Grande - Campus Patos. In the methodology, the collection was performed with the aid of sterile swabs on different surfaces of the dental clinical environment and to identify the strains of SCP, the following tests were carried out: Gram stain, fermentation of mannitol agar, catalase production and slide coagulase. As a result, we obtained the presence of SCP in all boxes of dental care and in all surfaces analyzed, highlighting the surface of the equipment, where in 80% of them the species was detected. The contamination index was 15%, 55%, 35% and 80% for the handle surfaces of the reflector, spitter, chair arm and equipment, respectively. Based on the results, it is concluded that the dental environment can be colonized by seriously pathogenic microorganisms such as SCP, therefore hygiene, disinfection and, above all, biosafety, must be prioritized in order to avoid potential contamination.